CORPORATE SOCIAL RESPONSIBILITY IN BANKING IN INDONESIA: THE ROLE OF INTELLECTUAL CAPITAL AND CHARACTERISTICS OF THE BOARD OF COMMISSIONERS - Annafi Nur Dwitarani; Bima Cinintya Pratama; Iwan Fakhruddin; Hardiyanto Wibowo (Bajang Institute, 2023)
This study aims to examine the influence of Intellectual Capital, the Board of Commissioners, and the Proportion of Independent Commissioners on Disclosure of Corporate Social Responsibility, with the population used in this study being bank companies registered with the Financial Services Authority (OJK) with a sample of 41 bank companies during the 2017 period -2021. This study uses panel data regression model analysis to test the hypothesis. The analysis techniques used in this study were descriptive statistical tests, preliminary tests ( Breusch-Pagan, likelihood tests, Hausman tests ), diagnostic tests (heteroscedasticity tests and autocorrelation tests), and hypothesis testing. Based on the results of the three preliminary tests in determining the panel data regression model, this study uses the fixed effect model to examine the relationship between variables in the regression model. The results of this study indicate that Intellectual Capital has a positive effect on CSR Disclosure, optimal utilization of Intellectual Capital resources can increase CSR quality disclosure more broadly. The Board of Commissioners variable has a negative effect on CSR disclosure, this shows that each additional member of the board of commissioners will have an impact on decreasing CSR disclosure. The independent board of commissioners proportion variable does not affect CSR disclosure because not all independent commissioners can demonstrate their independence so the oversight function does not function properly in conducting CSR disclosures.